CULTIVATION OF CITRONELLA AND ITS OIL EXTRACTION - Tewari, Priyadarshini Avadhesh; Mohan, Rakesh (Innoriginal: International Journal of Sciences, 2014)
Citronella grass cultivation is commercially done for its aromatic oil. Oil contains Citral which has odour like lemon, thatâ€™s why the grass is also known as Lemon grass. Scientific methods of cultivation give good yield and the appropriate time of harvest gives good quality of oil. Oil of Java citronella is of superior quality. Aromatic oil obtained by the method of steam distillation is useful in cosmetic industry, perfumes, soaps and detergents; also it is used for medicinal purpose. Thus farmers can get good money by cultivation of aromatic grasses. Â